Uji Aktivitas Antiinflamasi Infusa Daun Afrika (Vernonia amygdalina) pada Tikus Putih yang Diinduksi Karagenan - Lusi Agus Setiani; Moerfiah Moerfiah; Yulianita Yulianita (Pharmacon: Jurnal Farmasi Indonesia, 2020)
Inflammation is one of the immune system's main responses to infection and irritation. One of the medicinal plants that can be used as anti-inflammatory is African leaves because there have flavonoid compounds. Flavonoid compounds have anti-inflammatory effects that can regulate arachidonic acid metabolism by inhibiting cyclooxygenase (COX) and lipooxygenase activity.This study aims to determine the effectiveness and determine the effective dose of African leaf infusion as anti-inflammatory in sparague dawley strain  induced carrageenan male white rats. The method used is measurement of udema with subplantar 1% carrageenan induction.Test animals used were 20 male rats divided into 5 groups. Each group consisted of 4 rats. Group I as a negative control was given CMC-Na solution, the second group as a positive control was given diclofenac sodium with 1.26 mg/200 gBB body weight, group III, IV and V were given African leaf infusion with three dose ratings namely 100, 150, 200 mg/kgBB bodyweight. The results showed that the infusion of African leaves had Antiinflammatory Activity with dose 200 mg/kg body weight as the most effective dose against inhibition of inflammation.